Investigation of Period-Lengthening Ratio for Single-Degree-of-Freedom Structures Using Dynamic Centrifuge Test. Issue 7 (7th June 2021) - Ko, Kil-Wan; Ha, Jeong-Gon; Park, Heon-Joon; Kim, Dong-Soo
ABSTRACT: Understanding of the soil-foundation-structure interaction (SFSI) is crucial for seismic design. The period-lengthening ratio (PLR) has been studied using both analytical and experimental methods. In this study, to obtain a PLR that reflects the non-linear characteristics of the soil, dynamic centrifuge testing is conducted and the PLR is evaluated for different seismic intensity and frequency characteristics. The results indicate that the PLR of a single-degree-of-freedom (SDOF) structure increases with the peak ground acceleration at the surface. In addition, from the test results, the PLR is affected by the relationship between the excitation and natural frequencies of the structure, which must be considered in future.